Photocureable coating containing pentaerythritol triallyl ether

By using the synergistic effect of pentaerythritol triallyl ether and nano-zirconia, the problem of reduced gloss caused by nano-silica in UV-curable coatings was solved, thereby improving the gloss and performance of the coating.

CN121064709APending Publication Date: 2025-12-05SHENZHEN PRECHEM FINE CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511466423.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-14
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

When nano-silica materials are added to existing UV-curable coatings to improve performance, the gloss of the coating is significantly reduced, which limits its application range.

Method used

Using pentaerythritol triallyl ether as the core material, PEAE-modified nanofiller composite mother liquor and active PEAE microspheres replace traditional nano silica, combined with nano zirconium oxide dispersion, to form a synergistic effect, improve coating gloss and enhance density, erosion resistance and hardness.

Benefits of technology

It significantly improves the gloss of the coating, enhances the density, erosion resistance and hardness of the paint, avoids the gloss reduction problem caused by nanomaterials, and forms a more stable coating structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121064709A_ABST
    Figure CN121064709A_ABST
Patent Text Reader

Abstract

The invention discloses a photocureable coating containing pentaerythritol triallyl ether and a preparation method thereof, and belongs to the field of coatings, the photocureable coating comprises the following components by weight: 100 parts of a photocureable oligomer matrix, 1-5 parts of a first photoinitiator, a composite nano filler and an auxiliary agent, the composite nano filler comprises 6 to 8 parts of PEAE modified nano filler composite mother liquor and 12 to 14 parts of active PEAE microspheres; the auxiliary agent comprises 3-5 parts of nano zirconium oxide dispersion liquid; the PEAE modified nanofiller composite mother liquor comprises a PEAE monomer and composite nanoparticles, and the mass ratio of the PEAE monomer to the composite nanoparticles is (4-5): 1; the active PEAE microspheres are obtained by taking pentaerythritol triallyl ether (PEAE), dipentaerythritol pentaacrylate, a second photoinitiator, a chain transfer agent, an emulsifier and deionized water as main raw materials, and irradiating the main raw materials through an emulsion polymerization method in combination with 80-85% of UV energy required by theoretical complete curing. On the basis of an existing photocuring system, the nano filler is improved, and the glossiness of the coating is relatively improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of coating processing and relates to a light-curing coating containing pentaerythritol triallyl ether. BACKGROUND

[0002] The light-curing coating has the advantages of short curing time, low curing temperature and low volatile content, and is a new coating variety with energy saving, resource saving, no pollution and high efficiency.

[0003] However, the light-curing coating has defects in hardness, erosion resistance and adhesion, and in order to improve the hardness, erosion resistance and adhesion of the coating, nano fillers are added to the light-curing coating, which has good improvement effect, but nano materials, especially nano silicon dioxide with extinction performance, can effectively improve the performance of the coating, but also significantly reduce the gloss of the coating, which is not suitable for environments or products requiring gloss, thereby limiting the use range of the light-curing coating containing nano materials. SUMMARY

[0004] The application aims to provide a light-curing coating containing pentaerythritol triallyl ether, which solves the problem that nano materials significantly reduce the gloss of the coating when adding nano materials containing silicon dioxide to the light-curing coating to improve the performance of the coating.

[0005] The technical scheme adopted by the application is as follows: A light-curing coating containing pentaerythritol triallyl ether comprises the following components in parts by weight: 100 parts of a light-curing oligomer matrix, 1-5 parts of a first photoinitiator, a composite nano filler and an auxiliary agent, wherein the composite nano filler comprises 6-8 parts of a PEAE modified nano filler composite mother liquor and 12-14 parts of active PEAE microspheres; and the auxiliary agent comprises 3-5 parts of a nano zirconium oxide dispersion liquid. The PEAE modified nano filler composite mother liquor comprises PEAE monomers and composite nano particles, and the mass ratio of the PEAE monomers to the composite nano particles is 4-5:1. The active PEAE microspheres are mainly prepared from pentaerythritol triallyl ether (PEAE), dipentaerythritol pentaacrylate, a second photoinitiator, a chain transfer agent, an emulsifier and deionized water by an emulsion polymerization method and irradiation with 80-85% of the theoretical complete curing required UV energy.

[0006] The extinction mechanism of extinction nano materials such as nano silicon dioxide mainly includes two points: one is that nano particles are easy to aggregate, increasing the roughness of the coating film surface; and the other is that the aggregates become strong light scattering centers, reflecting the incident light in disorder to all directions (diffuse reflection), reducing the reflection intensity of the substrate; the significant reduction of the gloss of the coating is mainly based on the synergistic effect of the above two reasons.

[0007] The application improves the nano filler based on the existing photocuring system, such as an epoxy acrylate photocuring system; the nano filler composite mother liquor modified by PEAE and the active PEAE microspheres replace the traditional pure inorganic nano materials such as nano silicon dioxide and nano zinc oxide; compared with the existing nano silicon dioxide reinforced photocuring coating, the principle of relatively improving the gloss of the coating is that: The application takes pentaerythritol triallyl ether as the core substance, and the molecular structure of the pentaerythritol triallyl ether has three double bonds and one hydroxyl group, and has multiple active sites; Firstly, the application takes pentaerythritol triallyl ether as the core substance, and solid microspheres are prepared to obtain solid pentaerythritol triallyl ether, which replaces part of the inorganic nano materials and plays a filling role in the coating, can enhance the compactness of the coating, and further improve the permeability, erosion resistance and hardness of the coating; secondly, the surface of the solid microspheres in the application is rich in unreacted double bonds, which can react with the oligomer matrix during the curing of the coating, and can improve the adhesion of the coating, and also avoids the interface defects such as phase separation and micropores caused by the physical combination of the traditional inorganic nano filler and the organic matrix, which is helpful to realize the smoothness and smoothness of the coating surface; Secondly, the active PEAE microspheres in the application replace part of the inorganic nano materials to improve the flatness and smoothness of the coating, and reduce the influence of the filler on the smoothness of the coating; on this basis, the application adds a nano zirconium oxide dispersion liquid, which can improve the gloss of the coating, and the surface of the nano zirconium oxide contains a hydroxyl group, which can form a hydrogen bond with the hydroxyl group of the active PEAE microspheres; after the microspheres are anchored in the coating, the gloss of the coating can be improved; the nano zirconium oxide and the active PEAE microspheres form a synergistic effect, the active PEAE microspheres improve the flatness and smoothness of the coating surface to reduce the influence of the filler on the gloss of the coating; and the addition of the nano zirconium oxide improves the gloss of the coating; the two synergistically improve the gloss of the coating compared with the prior art; Finally, in order to realize the particle gradation, on the basis of the active PEAE microspheres (micron-sized particle size) provided, in order to further improve the compactness, hardness, wear resistance and the like of the coating, the application introduces composite nanoparticles, taking nanometer silicon dioxide as the main particle, in order to ensure the uniform dispersion of the nanoparticles in the coating and the anchoring during solidification, and to avoid the formation of nanoparticle aggregates; the application configures a PEAE modified nanofiller composite mother liquor with PEAE monomers and composite nanoparticles, which contains liquid PEAE and PEAE modified nanoparticles at the same time; the hydroxyl groups in pentaerythritol triallyl ether can form a modification layer on the surface of the nanoparticles, producing a steric hindrance effect, so that the nanoparticles are uniformly dispersed in the coating matrix, and under the driving of the liquid PEAE, they can fully fill the pores and play a filler role in cooperation with the active PEAE microspheres; the liquid PEAE, as a flowable monomer, is mixed with the oligomer matrix to form a continuous crosslinked network matrix; the solid PEAE acts as a crosslinking node of the crosslinked network and chemically anchors the matrix through multiple double bonds on its surface; the two form a mode similar to point-surface combination, which helps to form a more stable coating structure and can adapt to various complex environments.

[0008] Further, the raw materials of the active PEAE microspheres include 18 parts of pentaerythritol triallyl ether (PEAE), 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of a second photoinitiator, 0.2 parts of a chain transfer agent, 1 part of an emulsifier, and 80 parts of deionized water.

[0009] Further, the active PEAE microspheres are prepared by the following method: A1, uniformly mix pentaerythritol triallyl ether (PEAE), dipentaerythritol pentaacrylate, a second photoinitiator, and a chain transfer agent to obtain a mixture A; A2, add an emulsifier to deionized water, stir and mix uniformly to obtain a mixture B; A3, under high-speed shearing, slowly add mixture A to component B to obtain a microemulsion; A4, under continuous stirring, UV irradiation is applied to the microemulsion, and the applied UV energy is 80-85% of the theoretical complete curing required UV energy, and a suspension is obtained by reaction; A5, the suspension is subjected to centrifugation, washing, and spray drying to obtain active PEAE microspheres.

[0010] Further, the second photoinitiator is photoinitiator Irgacure 819; the chain transfer agent is mercaptopropionic acid; and the emulsifier is 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86.

[0011] Further, the PEAE modified nanofiller composite mother liquor is prepared by the following method: mixing PEAE monomer, silane coupling agent KH570 and composite nanoparticles in proportion to obtain a mixture, dispersing the mixture using a high-speed dispersing machine to obtain a uniform slurry, transferring the slurry to a sand mill for grinding to obtain the PEAE modified nanofiller composite mother liquor; wherein the amount of silane coupling agent KH570 is 3% of the mass of the composite nanoparticles.

[0012] Further, the composite nanoparticles include nanosilica and nanoalumina, and the mass ratio of the nanosilica to the nanoalumina is 3:1.

[0013] Further, the auxiliary agent further includes 0.3-0.5 parts of byk361N leveling agent and 0.2-0.3 parts of BYK-055 defoaming agent.

[0014] Further, the photocurable oligomer matrix includes epoxy acrylate resin, polyurethane acrylate oligomer and bifunctional acrylate monomer at a mass ratio of 2:1:1; and the first photoinitiator includes benzoin ethyl ether and benzophenone at a mass ratio of 2:1.

[0015] Further, the UV energy required for theoretical complete curing is 450 mJ / cm 2 ; wherein the UV energy (mJ / cm²) = UV intensity (mW / cm²) x irradiation time (S), and the judgment standard for theoretical complete curing is that the dry weight of the microspheres has no loss after being soaked in tetrahydrofuran solvent for 24 hours; when the UV energy is lower than 450 mJ / cm 2 , the dry weight of the microspheres will be lost after being soaked in tetrahydrofuran solvent for 24 hours, therefore, 450 mJ / cm 2 is taken as the UV energy required for theoretical complete curing under the active PEAE microsphere formula.

[0016] A preparation method of a photocurable coating containing pentaerythritol triallyl ether, comprising the following steps: S1, uniformly mixing epoxy acrylate resin, polyurethane acrylate oligomer and bifunctional acrylate monomer at a mass ratio of 2:1:1 to obtain a photocurable oligomer matrix; S2, slowly adding active PEAE microspheres and nanometer zirconium oxide dispersion liquid in the auxiliary agent into the photocurable oligomer matrix under stirring, uniformly stirring, then slowly adding PEAE modified nanofiller composite mother liquor under stirring, continuing to stir for 30-40 minutes after the addition is completed; then, adding a first photoinitiator and other components in the auxiliary agent under stirring, stirring for another 30-40 minutes after the addition is completed, stopping stirring, and vacuum degassing to obtain the photocurable coating containing pentaerythritol triallyl ether.

[0017] To sum up, the beneficial effects of the present application are as follows: 1. The photocuring coating containing pentaerythritol triallyl ether of the present application is based on the existing photocuring system, and the nano filler is improved, the nano filler composite mother liquor modified by PEAE and active PEAE microspheres are used to replace the traditional pure inorganic nano materials such as nano silicon dioxide and nano zinc oxide, compared with the existing nano silicon dioxide enhanced photocuring coating, the gloss of the coating is significantly improved. 2. In the present application, the active PEAE microspheres improve the gloss of the coating by improving the smoothness of the coating surface, and the addition of nano zirconium oxide improves the gloss of the coating, and the two are synergistic, compared with the prior art, the gloss of the coating is significantly improved. 3. In the present application, liquid PEAE is mixed with oligomer matrix to form a continuous crosslinked network matrix, and solid PEAE is used as a crosslinking node of the crosslinked network, and the surface of the solid PEAE is chemically anchored to the matrix through multiple double bonds; the two form a mode similar to point and surface combination, which helps to form a more stable coating structure and can adapt to various complex environments. 4. The present application uses pentaerythritol triallyl ether as the core material to prepare solid microspheres, and obtains solid pentaerythritol triallyl ether, which replaces part of the inorganic nano materials and plays a filling role in the coating, which can enhance the compactness of the coating, and then improve the permeability, erosion resistance and hardness of the coating; secondly, the surface of the solid microspheres in the present application is rich in unreacted double bonds, which can react with the oligomer matrix during the curing of the coating, and can improve the adhesion of the coating, and also avoids the interface defects such as phase separation and microporous holes caused by the physical combination of traditional inorganic nano fillers and organic matrix, which helps to realize the smoothness of the coating surface. BRIEF DESCRIPTION OF DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments, and it should be understood that the following drawings only show some embodiments of the present application, and should not be regarded as a limitation to the scope, and for those skilled in the art, other related drawings can also be obtained without creative labor on the basis of these drawings, wherein: Figure 1 is the SEM graph of the active PEAE microspheres prepared in Example 4; Figure 2 is a comparison graph of the use effect of Example 4. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application, that is, the described embodiments are only a part of the embodiments of the present application, but not all the embodiments. The components of the embodiments of the present application generally described and shown in the accompanying drawings can be arranged and designed in various different configurations.

[0020] Therefore, the detailed description of the embodiments of the present application provided below in the accompanying drawings is not intended to limit the scope of the claimed present application, but only represents selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative efforts are within the scope of protection of the present application.

[0021] It should be noted that the relational terms such as "first" and "second" and the like are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "contain" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or device. Without more limitations, the element defined by the statement "including a" does not exclude the presence of additional identical elements in the process, method, article or device including the element.

[0022] The features and performances of the present application will be further described in detail below with reference to the embodiments.

[0023] The light-cured coating containing pentaerythritol triallyl ether provided by the embodiments of the present application comprises the following components in parts by weight: 100 parts of a light-cured oligomer matrix, 1-5 parts of a first photoinitiator, 6-8 parts of a PEAE modified nanofiller composite mother liquor, 12-14 parts of active PEAE microspheres, 3-5 parts of a nanometer zirconium oxide dispersion, 0.3-0.5 parts of byk361N leveling agent, and 0.2-0.3 parts of BYK-055 defoaming agent. The light-cured oligomer matrix comprises epoxy acrylate resin, polyurethane acrylate oligomer and difunctional acrylate monomer in a mass ratio of 2:1:1; the first photoinitiator comprises benzoin ethyl ether and benzophenone in a mass ratio of 2:1. The PEAE modified nanofiller composite mother liquor comprises PEAE monomers and composite nanoparticles, and the mass ratio of the PEAE monomers to the composite nanoparticles is 4-5:1; the PEAE modified nanofiller composite mother liquor is prepared by the following method: PEAE monomers, silane coupling agent KH570 and composite nanoparticles are mixed in proportion, the composite nanoparticles comprise nanosilica and nanoalumina, and the mass ratio of the nanosilica to the nanoalumina is 3:1, to obtain a mixture; the mixture is dispersed by using a high-speed dispersion machine to obtain a uniform slurry; and the slurry is transferred to a sand mill for grinding, to obtain the PEAE modified nanofiller composite mother liquor; wherein the amount of the silane coupling agent KH570 is 3% of the mass of the composite nanoparticles; The raw materials of the active PEAE microspheres, calculated separately, comprise 18 parts of pentaerythritol triallyl ether, 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of a photoinitiator Irgacure 819 (second photoinitiator), 0.2 parts of a mercaptopropionic acid chain transfer agent, 1 part of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier, 80 parts of deionized water, and are prepared by the following method: A1, the pentaerythritol triallyl ether, the dipentaerythritol pentaacrylate, the second photoinitiator and the chain transfer agent are uniformly mixed to obtain a mixture A; A2, the emulsifier is added to the deionized water, and stirred and mixed uniformly to obtain a mixture B; A3, under high-speed shearing, the mixture A is slowly added to component B to obtain a microemulsion; A4, under continuous stirring, the microemulsion is subjected to UV irradiation reaction, and the applied UV energy is 80-85% of the theoretical complete curing required UV energy, and a suspension is obtained by the reaction; the theoretical complete curing required UV energy is 450 mJ / cm 2 ; wherein, the UV energy (mJ / cm²) = UV intensity (mW / cm²) x irradiation time (S); A5, the suspension is subjected to centrifugation, washing and spray drying to obtain the active PEAE microspheres.

[0024] The preparation method of the photocuring coating containing pentaerythritol triallyl ether comprises the following steps: S1, epoxy acrylate resin, polyurethane acrylate oligomer and bifunctional acrylate monomer are mixed in a mass ratio of 2:1:1 to obtain a photocuring oligomer matrix; S2, slowly add the active PEAE microspheres and the nano zirconium oxide dispersion liquid in the auxiliary agent into the photocuring oligomer matrix under stirring, after uniform stirring, slowly add the PEAE modified nano filler composite mother liquor under stirring, continue stirring for 30-40 minutes after the addition is completed; then, add the first photoinitiator and other components in the auxiliary agent under stirring, stir for another 30-40 minutes after the addition is completed, stop stirring, and perform vacuum degassing after standing to obtain the photocuring coating containing pentaerythritol triallyl ether.

[0025] The use mode of the photocuring coating is as follows: before construction, the coating needs to be stirred by a mechanical stirrer at a speed of 300-500 rpm for 10-15 minutes; The curing mode is as follows: mild hot air at 40-50℃ is used for pre-drying for 1-2 minutes, then ultraviolet light at a power of 100 mW / cm 2 is used for irradiation for 10-15 seconds, and finally ultraviolet light at a power of 150 mW / cm 2 is used for irradiation for about 6-8 seconds.

[0026] Example 1 The embodiment provides a photocuring coating containing pentaerythritol triallyl ether, which comprises the following components in parts by weight: 100 parts of a photocuring oligomer matrix, 1 part of a first photoinitiator, 6 parts of a PEAE modified nano filler composite mother liquor, 12 parts of active PEAE microspheres, 3 parts of a nano zirconium oxide dispersion liquid, 0.3 parts of byk361N leveling agent, and 0.2 parts of BYK-055 defoaming agent; the photocuring oligomer matrix comprises epoxy acrylate resin, polyurethane acrylate oligomer, and bifunctional acrylate monomer (tripropylene glycol diacrylate) at a mass ratio of 2:1:1; the first photoinitiator comprises benzoin ether and benzophenone at a mass ratio of 2:1; The PEAE modified nano filler composite mother liquor comprises PEAE monomers and composite nanoparticles, and the mass ratio of the PEAE monomers to the composite nanoparticles is 4:1, and is prepared by the following method: PEAE monomers, silane coupling agent KH570, and composite nanoparticles are mixed in proportion, the composite nanoparticles comprise nano silicon dioxide and nano aluminum oxide, and the mass ratio of the nano silicon dioxide to the nano aluminum oxide is 3:1, a mixture is obtained, a uniform slurry is obtained after the mixture is dispersed by using a high-speed dispersion machine, and the slurry is transferred to a sand mill for grinding to obtain the PEAE modified nano filler composite mother liquor; wherein, the addition amount of the silane coupling agent KH570 is 3% of the mass of the composite nanoparticles; The raw materials for the active PEAE microspheres include 18 parts of pentaerythritol triallyl ether, 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of a photoinitiator Irgacure 819, 0.2 parts of a mercaptopropionic acid chain transfer agent, 1 part of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier, 80 parts of deionized water, and are prepared by the following method: A1, uniformly mix pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, photoinitiator Irgacure 819, and mercaptopropionic acid chain transfer agent to obtain a mixture A; A2, add 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier to deionized water, and stir to mix uniformly to obtain a mixture B; A3, slowly add mixture A to component B under high-speed shearing to obtain a microemulsion; A4, under continuous stirring, UV irradiate the microemulsion, apply a UV energy of 80% of the theoretical UV energy required for complete curing, and react to obtain a suspension; the theoretical UV energy required for complete curing is 450 mJ / cm 2 ; A5, centrifuge, wash, and spray dry (120°C inlet / 75°C outlet) the suspension to obtain active PEAE microspheres.

[0027] The above method for preparing a photocurable coating containing pentaerythritol triallyl ether includes the following steps: S1, uniformly mix an epoxy acrylate resin, a polyurethane acrylate oligomer, and a difunctional acrylate monomer to obtain a photocurable oligomer matrix; S2, slowly add active PEAE microspheres and a nano-zirconium oxide dispersion to the photocurable oligomer matrix under stirring, uniformly stir, then slowly add a PEAE-modified nano-filler composite mother liquor under stirring, continue stirring for 35 minutes after the addition is complete, then add a first photoinitiator, byk361N leveling agent, and BYK-055 defoaming agent under stirring, stir for another 40 minutes after the addition is complete, stop stirring, and perform vacuum degassing while standing to obtain the photocurable coating containing pentaerythritol triallyl ether.

[0028] Example 2 The embodiment is based on example 1, and different from example 1: the photo-curable coating containing pentaerythritol triallyl ether provided by the embodiment includes the following components in parts by weight: 100 parts of photo-curable oligomer matrix, 3 parts of first photoinitiator, 7 parts of PEAE modified nanofiller composite mother liquor, and 13 parts of active PEAE microspheres, 4 parts of nanometer zirconium oxide dispersion, 0.4 parts of byk361N leveling agent, and 0.3 parts of BYK-055 defoaming agent; the remaining parts are consistent with example 1.

[0029] Example 3 The embodiment is based on example 1, and different from example 1: the photo-curable coating containing pentaerythritol triallyl ether provided by the embodiment includes the following components in parts by weight: 100 parts of photo-curable oligomer matrix, 3 parts of first photoinitiator, 7 parts of PEAE modified nanofiller composite mother liquor, and 13 parts of active PEAE microspheres, 4 parts of nanometer zirconium oxide dispersion, 0.4 parts of byk361N leveling agent, and 0.3 parts of BYK-055 defoaming agent; the remaining parts are consistent with example 1.

[0030] Example 4 The embodiment is based on example 2, and different from example 2: the UV energy of UV irradiation in the preparation process of active PEAE microspheres is different, specifically: The raw materials of the active PEAE microspheres include 18 parts of pentaerythritol triallyl ether, 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of photoinitiator Irgacure 819, 0.2 parts of mercaptopropionic acid chain transfer agent, 1 part of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier, 80 parts of deionized water, and is prepared by the following method: A1, uniformly mix pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, photoinitiator Irgacure 819, and mercaptopropionic acid chain transfer agent to obtain mixture A; A2, add 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier to deionized water, and stir to mix uniformly to obtain mixture B; A3, slowly add mixture A to component B under high-speed shearing to obtain a microemulsion; A4, under continuous stirring, UV irradiate the microemulsion, and the applied UV energy is 83% of the theoretical complete curing required UV energy, and the reaction obtains a suspension; the theoretical complete curing required UV energy is 450 mJ / cm 2 ; A5, the suspension is centrifuged, washed, and spray-dried (120°C inlet / 75°C outlet) to obtain the active PEAE microspheres. The rest is the same as in Example 2. The SEM image of the active PEAE microspheres prepared in this example is shown in FIG. 1, and a regular microsphere structure can be obtained. Figure 1

[0031] Example 5 This example is based on Example 2, except that the UV energy used in the UV irradiation during the preparation of the active PEAE microspheres is different from that in Example 2. Specifically, the UV energy used in the UV irradiation is 85% of the theoretical UV energy required for complete curing. The raw materials for the active PEAE microspheres include 18 parts of pentaerythritol triallyl ether, 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of photoinitiator Irgacure 819, 0.2 parts of mercaptopropionic acid chain transfer agent, 1 part of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier, 80 parts of deionized water, and are prepared by the following method: A1, uniformly mix the pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, photoinitiator Irgacure 819, and mercaptopropionic acid chain transfer agent to obtain a mixture A; A2, add the 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier to the deionized water, and stir to mix uniformly to obtain a mixture B; A3, slowly add the mixture A to component B under high-speed shearing to obtain a microemulsion; A4, under continuous stirring, UV irradiate the microemulsion, and the applied UV energy is 85% of the theoretical UV energy required for complete curing, and the reaction obtains a suspension; the theoretical UV energy required for complete curing is 450 mJ / cm 2 ; A5, the suspension is centrifuged, washed, and spray-dried (120°C inlet / 75°C outlet) to obtain the active PEAE microspheres. The rest is the same as in Example 2.

[0032] Example 6 This example is based on Example 2, except that in this example, the PEAE modified nanofiller composite mother liquor includes PEAE monomers and composite nanoparticles, and the mass ratio of the PEAE monomers to the composite nanoparticles is 5:1.

[0033] Comparative Example 1 (blank group, prior art, only inorganic nanoparticles) ​Based on Example 2, the difference from Example 2 is that: the photocurable coating containing pentaerythritol triallyl ether provided in this comparative example includes the following components in parts by weight: 100 parts of photocurable oligomer matrix, 3 parts of first photoinitiator, 20 parts of composite nanoparticles, 0.4 parts of BYK361N leveling agent, and 0.3 parts of BYK-055 defoamer; wherein, the composite nanoparticles include nano-silica and nano-alumina, and the mass ratio of nano-silica to nano-alumina is 3:1; the preparation method of the coating is the same as that in Example 1.

[0034] Comparative Example 2 Based on Example 4, the difference from Example 4 is that the photocurable coating containing pentaerythritol triallyl ether provided in this comparative example does not include PEAE-modified nanofiller composite mother liquor, but all other aspects are the same.

[0035] Comparative Example 3 Based on Example 4, the difference from Example 4 is that the photocurable coating containing pentaerythritol triallyl ether provided in this comparative example does not include active PEAE microspheres, but all other aspects are the same.

[0036] Comparative Example 4 Based on Example 2, the difference from Example 2 is that the preparation conditions of the active PEAE microspheres in this comparative example are different, specifically: Calculated individually, the active PEAE microspheres are prepared from the following raw materials: 18 parts pentaerythritol triallyl ether, 2 parts dipentaerythritol pentaacrylate, 0.4 parts photoinitiator Irgacure 819, 0.2 parts mercaptopropionic acid chain transfer agent, 1 part 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier, and 80 parts deionized water, by the following method: A1. Mix pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, photoinitiator Irgacure 819, and mercaptopropionic acid chain transfer agent uniformly to obtain mixture A; A2. Add 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier to deionized water and stir to mix evenly to obtain mixture B; A3. Under high-speed shearing, mixture A is slowly added to component B to obtain a microemulsion; A4. Under continuous stirring, the microemulsion is subjected to UV irradiation reaction, with the applied UV energy being the theoretically required UV energy for complete curing, resulting in a suspension; the theoretically required UV energy for complete curing is 450 mJ / cm². 2 ; A5, the suspension is centrifuged, washed, and spray dried (120°C inlet / 75°C outlet) to obtain the active PEAE microspheres. The rest is consistent with Example 2.

[0037] Comparative Example 5 Based on Example 2, the difference between Example 2 and the present comparative example is that the preparation conditions of the active PEAE microspheres in the present comparative example are different, specifically: Based on Example 2, the difference between Example 2 and the present comparative example is that the preparation conditions of the active PEAE microspheres in the present comparative example are different, specifically: The raw materials for the active PEAE microspheres alone include 18 parts of pentaerythritol triallyl ether, 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of photoinitiator Irgacure 819, 0.2 parts of mercaptopropionic acid chain transfer agent, 1 part of 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier, 80 parts of deionized water, and are prepared by the following method: A1, uniformly mix the pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, photoinitiator Irgacure 819, and mercaptopropionic acid chain transfer agent to obtain a mixture A; A2, add the 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86 emulsifier to the deionized water, and stir to mix uniformly to obtain a mixture B; A3, slowly add the mixture A to component B under high-speed shearing to obtain a microemulsion; A4, under continuous stirring, UV irradiate the microemulsion, and the applied UV energy is 75% of the theoretical complete curing required UV energy, and the reaction obtains a suspension; the theoretical complete curing required UV energy is 450 mJ / cm 2 ;

[0038] Comparative Example 6 Based on Example 4, the difference between Example 4 and the present comparative example is that the photocurable coating containing pentaerythritol triallyl ether provided in the present comparative example does not include a nano-zirconium oxide dispersion liquid.

[0039] Comparative Example 7 Based on Example 4, different from Example 4 is that: the light-cured coating containing pentaerythritol triallyl ether provided by the present comparative example includes the following components in parts by weight: 100 parts of light-cured oligomer matrix, 3 parts of first photoinitiator, 7 parts of composite nanoparticles and 13 parts of active PEAE microspheres, 4 parts of nano zirconium oxide dispersion, 0.4 parts of byk361N leveling agent, 0.3 parts of BYK-055 defoaming agent; the composite nanoparticles include nanosilica, nanoalumina, and the mass ratio of nanosilica to nanoalumina is 3:1; the rest is consistent with Example 4.

[0040] Comparative Example 8 Based on Example 1, different from Example 1 is that: the mass ratio of PEAE monomer to composite nanoparticles in the present comparative example is 3:1, and the rest is consistent.

[0041] Comparative Example 9 Based on Example 1, different from Example 1 is that: the present comparative example does not include difunctional acrylate monomer (tripropylene glycol diacrylate) in the light-cured oligomer matrix, and the rest is consistent.

[0042] Comparative Example 10 Based on Example 4, different from Example 4 is that: the present comparative example does not include dipentaerythritol pentaacrylate in the active PEAE microspheres, and the rest is consistent.

[0043] Comparative Example 11 Based on Example 4, different from Example 4 is that: the present comparative example does not include mercaptopropionic acid chain transfer agent in the active PEAE microspheres, and the rest is consistent.

[0044] Comparative Example 12 Based on Example 4, different from Example 4 is that: the present comparative example does not include composite nanoparticles, and the mother liquor only has PEAE monomer.

[0045] Test Example 1 The workability of the coatings prepared in Examples 1-6 and Comparative Examples 1-12 was detected, and the results are shown in Table 1. The detection method is: 1, according to the national standard GB / T 6753.6-1986 "Large area brushing test of paint products", whether obvious resistance, wire drawing, bubble, sagging and other phenomena appear during brushing of the paint on different test panels is observed; if the paint shows smooth performance during brushing, no obvious adverse phenomena appear, then it can be evaluated as "no barrier to application", which indicates that the construction performance of the paint is good; the test panels include birch plywood (size not less than 1.0mx0.9mx0.006m), steel plate (size not less than 1.0mx1.0mx0.00123m), hard fiber board (size not less than 1.0mx0.9mx0.005m, the smooth side is the painted side), asbestos-cement board (double-pressed asbestos-cement board, size not less than 1.0mx0.8mx0.006m); 2, detect whether the paint slurry before brushing contains obvious lumps and other abnormal conditions visible to the naked eye.

[0046] Table 1 Coating construction performance test results The paint slurry prepared by the application is stable, uniform in texture, and has no barrier to application on various substrates, has a relatively wide range of use, and can be used on wood, steel plate and other substrates.

[0047] Test example 2 The basic properties of the coating cured from the paint in examples 1-6, comparative examples 1, 2, 3, 4, 6, 8, 10, 12 are detected, and the results are shown in Table 2.

[0048] The detection method is: 1. Gloss detection, refer to national standard GB / T 9754-2007, detection angle of gloss meter is 60°; 2. Adhesion; grid method, refer to GB / T 9286-2021 "Grid test of color paint and varnish" standard; 3. Pencil hardness: detected according to national standard GB6739-86 "Film hardness pencil hardness method"; 4. Resistance to washing: refer to standard GB / T 9266-2009; 5. VOC content: refer to national standard 100g / L, GB30981-2020; The specific steps of the above detection methods are prior art, which will not be described in detail here.

[0049] Table 2 Basic performance test results of the coating Compared with the comparative file 1, the application significantly improves the gloss of the coating layer on the basis of using nano-silicon dioxide. Based on example 4, the use effect (test effect) of comparative example 4 is shown in the table, and the gloss of the coating layer of example 4 is better. Figure 2

[0050] The above only describes the preferred embodiments of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement and improvement made by any person skilled in the art within the spirit and principle of the present application shall be included in the protection scope of the present application.​

Claims

1. A photocuring coating containing pentaerythritol triallyl ether, comprising the following components by weight: 100 parts of a photocuring oligomer matrix, 1-5 parts of a first photoinitiator, a composite nano-filler, an auxiliary agent, characterized in that: The composite nano-filler includes 6-8 parts of PEAE modified nano-filler composite mother liquor and 12-14 parts of active PEAE microspheres; the auxiliary agent includes 3-5 parts of nano-zirconium oxide dispersion liquid; The PEAE modified nano-filler composite mother liquor includes PEAE monomer and composite nano-particles, and the mass ratio of the PEAE monomer to the composite nano-particles is 4-5:

1. The active PEAE microspheres are prepared by an emulsion polymerization method and irradiation of 80-85% of the theoretical complete curing required UV energy, with pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, a second photoinitiator, a chain transfer agent, an emulsifier and deionized water as main raw materials.

2. The photocurable coating containing pentaerythritol triallyl ether according to claim 1, characterized in that: The raw materials of the active PEAE microspheres include 18 parts of pentaerythritol triallyl ether, 2 parts of dipentaerythritol pentaacrylate, 0.4 parts of a second photoinitiator, 0.2 parts of a chain transfer agent, 1 part of an emulsifier and 80 parts of deionized water, calculated separately from the active PEAE microspheres.

3. A photocurable coating containing pentaerythritol triallyl ether according to claim 2, characterized in that: The active PEAE microspheres are prepared by the following method: A1, uniformly mix pentaerythritol triallyl ether, dipentaerythritol pentaacrylate, a second photoinitiator and a chain transfer agent to obtain a mixture A; A2, add the emulsifier to the deionized water, stir and mix uniformly to obtain a mixture B; A3, slowly add the mixture A to component B under high-speed shearing to obtain a microemulsion; A4, continuously stir the microemulsion and irradiate it with UV, and the applied UV energy is 80-85% of the theoretical complete curing required UV energy, to obtain a suspension; A5, centrifuge, wash and spray dry the suspension to obtain the active PEAE microspheres.

4. The photocurable coating containing pentaerythritol triallyl ether according to claim 2, characterized in that: The second photoinitiator is photoinitiator Irgacure 819; the chain transfer agent is mercaptopropionic acid; and the emulsifier is 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate DNS-86.

5. The photocurable coating containing pentaerythritol triallyl ether according to claim 1, characterized in that: The PEAE modified nano-filler composite mother liquor is prepared by the following method: mix PEAE monomer, silane coupling agent KH570 and composite nano-particles in proportion to obtain a mixture, disperse the mixture with a high-speed dispersion machine to obtain a uniform slurry, transfer the slurry to a sand mill for grinding to obtain the PEAE modified nano-filler composite mother liquor; wherein the amount of the silane coupling agent KH570 is 3% of the mass of the composite nano-particles.

6. The photocurable coating containing pentaerythritol triallyl ether according to claim 1, characterized in that: The composite nano-particles include nano-silicon dioxide and nano-aluminum oxide, and the mass ratio of the nano-silicon dioxide to the nano-aluminum oxide is 3:

1.

7. The photocurable coating containing pentaerythritol triallyl ether according to claim 1, characterized by: The auxiliary agent further includes 0.3-0.5 parts of byk361N leveling agent and 0.2-0.3 parts of BYK-055 defoaming agent.

8. The photocurable coating containing pentaerythritol triallyl ether according to claim 1, characterized in that: The photocuring oligomer matrix includes epoxy acrylate resin, polyurethane acrylate oligomer and bifunctional acrylate monomer in a mass ratio of 2:1:1; and the first photoinitiator includes benzoin ethyl ether and benzophenone in a mass ratio of 2:

1.

9. The photocurable coating containing pentaerythritol triallyl ether according to claim 3, characterized by: The theoretical total curing required UV energy is 450 mJ / cm 2 ; wherein UV energy (mJ / cm2) = UV intensity (mW / cm2) x irradiation time (S).

10. A process for the preparation of a photocurable coating containing pentaerythritol triallyl ether according to any one of claims 1 to 9, characterized in that: The method includes the following steps: S1, mix epoxy acrylate resin, polyurethane acrylate oligomer and bifunctional acrylate monomer in a mass ratio of 2:1:1 to obtain a photocuring oligomer matrix; S2, under stirring, slowly add the active PEAE microspheres and the nano zirconium oxide dispersion in the auxiliary into the photocuring oligomer matrix, after stirring evenly, slowly add the PEAE modified nano filler composite mother liquor under stirring, continue stirring for 30-40 minutes after the feeding is completed; then, add the first photo initiator and other components in the auxiliary under stirring, stir for another 30-40 minutes after the feeding is completed, stop stirring, and carry out vacuum degassing by standing to obtain the photocuring coating containing pentaerythritol triallyl ether.